Transformasi Desa Kembang Seri Melalui KKN Basis Masjid: Fokus Pada Religi, Kesehatan, Pendidikan, dan Lingkungan - Yusnelma Eka Afri; Miko Harbiansa; Mardiana, Della; Anggun Citra Wardani; Restu Septawati; Anggun Tamara Tamesty; Ellita; Sepia Febrianti; Azizah Yuri Darazti; Agung Rahmat Hidayat; Muhammad Haviz Wahyudi (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
This study explores the transformation of Desa Kembang Seri through a community service program based on mosque initiatives, focusing on religious, health, educational, and environmental aspects. The primary issues addressed include the need for improved public health, enhanced religious education, and better environmental management. The objective is to implement health promotion activities, strengthen religious education, and engage in environmental rehabilitation to benefit the local community. The methodology employed includes a variety of community activities such as heart-healthy exercise sessions, religious teaching at TPQ Masjid Baitul Hamdi, health services at Posyandu, and bamboo planting for riverbank rehabilitation. The study finds that these activities significantly improved community health awareness, religious involvement, and environmental conditions. The program fostered a stronger social bond within the community and encouraged active participation in various initiatives. This approach demonstrates the effectiveness of integrating mosque-based activities into community development efforts.